Blood pressure in children with sickle cell disease is higher than in the general pediatric population - Juan C. Kupferman; Janet E. Rosenbaum; Marc B. Lande; Stella Stabouli; Yongsheng Wang; Daniella Forman; Dimitrios I. Zafeiriou; Steven G. Pavlakis (BMC, 2022)
Abstract Background Sickle cell disease (SCD) is associated with an increased risk of cardiovascular disease that may be due to a variety of possible risk factors, including abnormal blood pressure. Blood pressure (BP) of children and adolescents with SCD has been reported to be lower compared to the BP of the general pediatric population. Methods To confirm this prior observation, we compared reference BP values for children with SCD with reference BP values of the general pediatric population. We hypothesized that children with SCD do not have lower BPs than children without SCD. Results Systolic BP differed for both males and females, over the different age groups between pediatric subjects with and without SCD. Systolic BP was higher in children with SCD, in both obese and non-obese populations. Diastolic BP did not differ between the groups. Conclusions Our analysis demonstrated that systolic BP values are indeed higher in children with SCD than in the general pediatric population. This finding is consistent with the most recent literature showing abnormal BP patterns in the SCD pediatric population utilizing 24-hour BP monitoring devices. This is an important step for recognizing abnormal BP as a risk factor for cardio- and neurovascular events in SCD.